ANALISIS DAYA SAING USAHATANI TEMBAKAU DI KABUPATEN SUMENEP - Devi Putri Fajariyah; Sri Widayanti; Nisa Hafi Idhoh Fitriana (Jurnal Ilmu-Ilmu Agribisnis, 2023)
This study aims to examine the competitiveness of tobacco cultivation in Sumenep Regency, the impact of government policies, and the sensitivity of changes in input and product prices to the competitiveness of the industry. This research utilized multistage random sampling as its sampling technique, involving 40 farmers as its total sample. The Policy Analysis Matrix (PAM) method was used for data analysis and hypothesis testing. Sensitivity analysis was performed to quantify changes in input and output costs in the tobacco farming sector. The results showed that tobacco farming in Sumenep Regency had a comparative advantage with a Domestic resource cost ratio (DRCR) < 1 of 0.32 and a competitive advantage with a Private cost ratio (PCR) value <1, which was 0.43. The Effective Protection Coefficient (EPC) value of 0.75, this indicated that the policy was not operated efficiently, revealed that government policies on the competitiveness of tobacco production in Sumenep Regency had not had a positive impact on farmers. A decreasing trend in producer surplus was also revealed by the Net Transfer (NT) value of -Rp 18,046,000, the Profitability Coefficient (PC) value of 0.62, which proved that farmers' profits were diminished in the merely existence of a policy, and the Subsidy Ratio to Producer (SRP) value of -0.226, which forces farmers to pay more than their offset production costs. The outcomes of the most thorough sensitivity research also indicated that tobacco farming currently has competitive and comparative advantages. Â Key words: comparative advantage, competitive advantage, tobacco farming